Mpox 2022 to 2025 Update: A Comprehensive Review on Its Complications, Transmission, Diagnosis, and Treatment - Rajesh Yadav; Anis Ahmad Chaudhary; Ujjwal Srivastava; Saurabh Gupta; Sarvesh Rustagi; Hassan Ahmed Rudayni; Vivek Kumar Kashyap; Sanjay Kumar (Viruses, 2025)
Monkeypox virus (Mpox virus) is a zoonotic orthopoxvirus that has gained increased global attention due to recent outbreaks. The current review reports the latest update of Mpox cases from 25 February 2022 to 29 April 2025. It also evaluates the possible major complications in human life caused by Mpox. In early 2022, more than 40 countries reported Mpox outbreaks. As of 12 June 2024, the global case count for the 2022–2023 Mpox outbreak was 97,281 confirmed cases, in 118 countries. The World Health Organization (WHO) declared the Mpox virus, a zoonotic disease, a public health emergency of international concern (PHEIC) on 14 August 2024. Mpox symptoms include fever, headache, muscle pain, and face-to-body rashes. The review also highlights Mpox virus replication, genomics, pathology, transmission, diagnosis, and antiviral therapies. The 2022 outbreak is also discussed in detail. The coinfection of HIV in patients infected with Mpox is also discussed. The evolving Mpox epidemiology has raised concerns about the disease’s increasing spread in non-endemic countries, emphasizing the urgent need for control and prevention. The discussion on preventive measures, including vaccination, suggests that cross-protection against Mpox may be possible using orthopoxvirus-specific antibodies. Although there are no specific antiviral drugs available, certain drugs, such as tecovirimat, cidofovir, and ribavirin, are worth considering.